EMOTIONAL DYNAMICS OF THE MAIN CHARACTER IN THE NOVEL LONDON LOVE STORY BY TISA TS: (Study of Literature Psychology) - Enus, Agusthinus Abraham; Haerussaleh; Huda, Nuril (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
The intrinsic element is the most important element in building a literary work, especially a novel. The objective of this research is to provide a classification of the emotional dynamics expressed by the main character in the fiction novel that is being analyzed. The data source is written data source in the form of London love story novel. This research uses a qualitative approach and belongs to the type of descriptive research. The problem that the author investigates in this study is how to classify the emotional dynamics of the main character in the novel London love story, as well as what causes those emotional dynamics of the main character in the novel London love story. The results revealed that there are 4 dynamics contained in the novel London Love Story by Tisa Ts. The 4 dynamics include: Basic emotions (pleasure, anger, fear, and sadness); Emotions associated with sensor stimulation; Emotions related to self-assessment; and Emotions related to other people. Further, we found 2 emotional dynamics in the novel London Love Story by Tisa TS included the dynamics of knowledge and the dynamics of feelings.